IMPLEMENTASI MODEL ATIK UNTUK MENINGKATKAN LITERASI NUMERASI PADA ANAK USIA 5-6 TAHUN DI TK MAMBAUL ULUM - Siti Istiadah; Gunawan; Ahmad Afandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Through the use of the ATIK Observe, Imitate, and Do Model, this study seeks to improve children's numeracy literacy, especially in understanding the symbols of numbers 1–10. Based on the results of observations, students' numeracy literacy in understanding the symbols of numbers 1–10 is still low, namely sometimes they are still wrong in writing or calculating numbers, such as writing them backwards, making it difficult to distinguish one number symbol from another. "Two cycles of Arikunto's design and classroom action research (CAR) were used in this project. Each cycle consisted of two meetings. This study involved 12 children of Mambaul Ulum Kindergarten Group B, 6 boys and 6 girls." Documentation and observation sheets were used. The results of the study showed an increase in understanding the symbols of numbers 1–10. Before receiving the Action, only 17% of children in group B were able to understand the symbols for numbers 1–10. Two meetings after the implementation of the ATIK model in Cycle I resulted in a 50% increase in ability. In other words, an increase of 33% from the pre-cycle at the first meeting to the second meeting in cycle I, which is in the very good category, and 17% for the good category. The increase increased to 85% in the very good category at the end of cycle II. If 85% of students achieve achievement in the good category, it is a criterion for learning success.